The Influence Of Work Planning, Work Quality, Supervision And Training On The Work Performance Of Staff At The Lahat Regency Inspectorate - Sugiarti Sugiarti; Sulbahri Madjir; Darmin Darmin (Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
The purpose of this study is to determine, analyze, and demonstrate the influence of work planning, work quality, supervision, and education, individually and collectively, on the work performance of employees at the Lahat Regency Inspectorate. The research method used in this study was quantitative, using a questionnaire distributed to respondents. Data quality was tested using validity, reliability, and normality tests. The analysis used descriptive and inferential analyses using statistical calculations using multiple regression formulas, partial simultaneous tests, and coefficients of determination. The analysis results showed that work planning significantly influenced the work performance of employees at the Lahat Regency Inspectorate. Work quality significantly influenced the work performance of employees at the Lahat Regency Inspectorate. Supervision significantly influenced the work performance of employees at the Lahat Regency Inspectorate. Education significantly influenced the work performance of employees at the Lahat Regency Inspectorate. Work planning, work quality, supervision, and education significantly influenced the work performance of employees at the Lahat Regency Inspectorate.